The Effectiveness of Forest Conservation Policies and Programs - Börner, J.; Schulz, D.; Wunder, Sven; Pfaff, A. (Annual Reviews, 2020)
The world's forests provide valuable contributions to people but continue to be threatened by agricultural expansion and other land uses. Counterfactual-based methods are increasingly used to evaluate forest conservation initiatives. This review synthesizes recent studies quantifying the impacts of such policies and programs. Extending past reviews focused on instrument choice, design, and implementation, our theory of change explicitly acknowledges context. Screening over 60,000 abstracts yielded 136 comparable normalized effect sizes (Cohen's d). Comparing across instrument categories, evaluation methods, and contexts suggests not only a lack of “silver bullets” in the conservation toolbox, but that effectiveness is also moderate on average. Yet context is critical. Many interventions in our sample were implemented in “bullet-proof” contexts of low pressure on natural resources. This greatly limits their potential impacts and suggests the need to invest further not only in understanding but also in better aligning conservation with local and global development goals.